Effect Of Is Spirulina Supplementation on Blood Haemoglobin (Hb) And Plasma Protein Level of HIV Infected Patients - Suryavanshi, Narendrakumar J.; Kamble, Rajkumar M.; Suryawanshi, Surekha N.; Pathade, Girish (Journal of Neonatal Surgery, 2025)
Drop in blood hemoglobin (Hb) and plasma protein level in HIV infected patient is commonly seen due to various reasons like ineffective functioning of body organs, diminished immune function, increased catabolism, low food intake, poor digestion and adverse effect of antiretroviral therapy. Study was conducted to examine the effect of spirulina supplementation on blood hemoglobin (Hb) and plasma protein level of HIV infected patient. Study included 62 HIV infected patients, T0 (control)- 29 patients (20 male, 9 female), T1 (Treatment) - 32 patient (23 male, 9 female). T1 (Treatment) were provided with 5 g/day of Spirulina supplementation in capsule form along with therapeutic diet for period of six months with their regular medical prescription. Data was collected at beginning and end of study and was statistically analyzed. Results reveled non-significant decrease in blood hemoglobin by -0.07 mg/dl (male) and -0.60 mg/dl (female) in control group. In T1 (Treatment) group blood hemoglobin increased by 0.067 mg/dl (female) and 0.83 mg/dl (male) which was significant. Plasma protein level found to decrease in by -0.185 mg/dl (male) and -0.34 mg/dl (female) in control group. In T1 (Treatment) group plasma protein level though nonsignificant increased by 0.28 mg/dl (male) and 0.19 mg/dl (female). Result revealed positive effect of spirulina supplementation on Blood hemoglobin (Hb) and plasma protein level of HIV infected patient